Science of cryopreservation in reproductive medicine – Embryos and oocytes as exemplars - Yurchuk, Taisiia; Petrushko, Maryna; Fuller, Barry (Early Human Development, 2018)
The modern successes of reproductive medicine are based on the achievements in the fields of artificial fertilization and cryobiology over the last 50 years. Cryopreservation of oocytes makes it possible to preserve their reproductive potential after surgical interventions, treatment of cancer, for delayed pregnancy and to use cells for donation. Cryopreservation of embryos allows not only to reduce the multiple pregnancies rate and to increase the cumulative pregnancy rate as a result of embryo transfer in the following favorable cycles of the patient, but is also a necessary procedure in case of genetic diagnosis or in the case of contraindications for embryo transfer in the stimulated cycle due to possible complications. However, the viability of cryopreserved oocytes and embryos depends on the degree of their cryo damage during the process of freeze-warming. In this regard, it is very important to develop such freezing protocols that minimize the damages caused by the intra- and extracellular ice crystal formation, toxic effect of high concentrations of cryoprotectants and osmotic stresses. The effectiveness of cryopreservation of gametes and embryos is assessed on the basis of morphological, functional and genetic changes in the cells after warming. Special attention should be paid to the ethical issues of assisted reproductive technology, including cryobiotech technologies, which in many countries remain open and in need of settlement.
Review paper